2021
DOI: 10.24114/cess.v6i2.22857
|View full text |Cite
|
Sign up to set email alerts
|

Pendiagnosa Daun Mangga Dengan Model Convolutional Neural Network

Abstract: Pertanian adalah salah satu sektor ekonomi yang terpenting di negara-negara Asia Tenggara. Saat ini, pembangunan ekonomi sangat bergantung pada pertanian. Seperti contoh Mangga, Manga juga merupakan bahan makanan yang dapat diolah menjadi berbagai jenis makanan yang lezat. Karena banyaknya manfaat pada buah ini tak jarang masyarakat ingin menanam pohon mangga untuk dibudidayakan dengan tujuan komersil maupun pribadi. Salah satu masalah utama yang menurunkan kualitas dan kuantitas manufaktur pertanian adalah pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The confusion matrix table is used to measure the performance of a classification model because it consists of many rows of test data that are predicted correctly and incorrectly by the classification model. Confusion matrix are a useful tool to analyze how well a clustering and classifier can recognize tuples from different classes [23].…”
Section: Confusion Matrixmentioning
confidence: 99%
“…The confusion matrix table is used to measure the performance of a classification model because it consists of many rows of test data that are predicted correctly and incorrectly by the classification model. Confusion matrix are a useful tool to analyze how well a clustering and classifier can recognize tuples from different classes [23].…”
Section: Confusion Matrixmentioning
confidence: 99%
“…His further research was conducted by Kusrini, et diseases in mangoes, it was found that the accuracy results using the VVG16 model achieved top validation with accuracy of 89% and 90% respectively [9]. Another study conducted by Tsabitah Ayu, et al using a model (CNN) to classify the types of mango leaves affected by pests and healthy obtained accuracy results of 0.96% [10].…”
Section: Introductionmentioning
confidence: 99%